Planktonic foraminifera fluxes and their response to the Asian Monsoon: insights from the Maldives, Indian Ocean - Cariño, Maria Caezare Mae R.; Peleo-Alampay, Alyssa M.; Wiesner, Martin G.; de Silva, Leopoldo P.; Lahajnar, Niko; Betzler, Christian; Fikree, Ibrahim; Lüdmann, Thomas (Frontiers in Earth Science, 2023)
This study describes seasonal changes in the fluxes of planktonic foraminifera in response to changes in environmental conditions during the Asian Monsoon. Sediment trap systems were deployed for a period of one year at two locations in the Maldives: Kardiva Channel and Inner Sea. Twenty-six (26) planktonic foraminifera were recognized, of which six species (Trilobatus sacculifer, Globorotalia menardii, Globigerinoides ruber, Globigerina siphonifera, Neogloboquadrina dutertrei, and G. bulloides) dominated the assemblage (82 -84%) in both sites. Planktonic foraminifera fluxes and chlorophyll-a concentrations are higher in the Inner Sea. Total planktonic foraminifera fluxes show preference to high nutrient conditions during monsoon periods. Planktonic foraminifera fluxes generally follow the trend of carbonate fluxes except during October-November 2014. Species flux generally reached maximum during the NE monsoon as a response to increase in nutrient concentration brought by the movement of the North Equatorial Current over the trap sites. The expansion of nutrientrich surface waters, occurring eastward during the SW monsoon and westward during the NE monsoon, led to an increase in the population of species dwelling in both shallow (T. sacculifer and G. ruber) and deep waters (N. dutertrei and G. bulloides). Dominance of shallow-dwelling species T. sacculifer and G. ruber throughout the sampling period suggests stable stratification of the water column. This supports the idea of wind-mixing rather than local upwelling as the driving force for enrichment of nutrients and subsequent increase in planktonic foraminifera fluxes. Lateral advection and resuspension in settling of particles to the traps is evident based on the presence of benthic foraminifera in the Inner Sea samples. These processes, however, did not significantly mask climate and surface ocean signals since there remains a clear correlation between planktonic foraminifera fluxes and environmental conditions.